(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The ergativity phenomenon was studied in a variety of languages, but, to the best of my knowledge, not in connection with Syrian Arabic. The primary objective of this paper is to shed light on apparent ergative constructions in Syrian Arabic. We begin by considering what an ergative construction really means, introducing the basic data. Then we use word order and agreement facts as arguments to support our assumption that what resembles a subject in apparent Syrian ergative clauses is not a subject, but a topic. لقد طُرِقت ظاهرة اللزوم في العديد من اللغات، إلاّ أنها، حسب أقصى معرفتي، لم تُعالَج في العربية السورية. يكمن الهدف الرئيس لهذه الورقة في تسليط الضوء على التراكيب اللازمة لزوماَ ظاهرياَ في العربية السورية. نستهل عملنا هذا بالتطرق إلى ما يُعنى بالجملة اللازمة بالفعل، إذ نستعرض المعطيات الأساسية. بعدها ننتقل لتناول حُجَّتين مُمَثَّلتين بـ رتب الكلمات والتطابق لدعم فرضيتنا القائلة أن ما يُشبه الفاعل في التراكيب اللازمة لزوماَ ظاهرياَ في العربية السورية ليس بفاعل، بل حالة من حالات الموضَعَة.